DEVELOPING ENGLISH SPEAKING AND WRITING MATERIALS THROUGH PROBLEM-BASED LEARNING (PBL): A PRELIMINARY STUDY AT ISLAMIC UNIVERSITIES IN BENGKULU - Riswanto, Riswanto; Khermarinah, Khermarinah (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study investigates how Problem-Based Learning (PBL) can be applied to develop more effective English speaking and writing materials for students in Islamic higher education in Indonesia. Current teaching resources are often generic and heavily focused on grammar, offering little relevance to students’ academic disciplines or religious backgrounds. As a result, learners struggle to connect what they study in the classroom with their real-life academic and spiritual contexts. Drawing on qualitative data from two institutions (UIN Fatmawati Sukarno Bengkulu and IAIN Curup), this research includes classroom observations, document analysis, and interviews with lecturers and department heads. The findings reveal that English materials in these programs often lack contextual relevance, fail to incorporate Islamic values, and are not supported by coherent curriculum planning. Additionally, many lecturers lack formal training in English for Specific Purposes (ESP), particularly in faith-based education. The study highlights the potential of a PBL approach, when thoughtfully adapted, to improve student engagement, foster communicative competence, and bridge the gap between English instruction and students’ academic and spiritual needs. Importantly, this study represents the initial Analysis phase of the ADDIE instructional design framework, laying the groundwork for future development, implementation, and evaluation of PBL-based English materials tailored to Islamic higher education.